2019
DOI: 10.1101/690461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Histone H2AK119 Mono-Ubiquitination is Essential for Polycomb-Mediated Transcriptional Repression

Abstract: The major function of Polycomb group proteins (PcG) is to maintain transcriptional repression to preserve cellular identity. This is exerted by two distinct repressive complexes, PRC1 and PRC2, that modify histones by depositing H2AK119ub1 and H3K27me3, respectively. Both complexes are essential for development and are deregulated in several types of human tumors. PRC1 and PRC2 exist in different variants and show a complex regulatory cross-talk. However, the contribution that H2AK119ub1 plays in mediating PcG… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 79 publications
5
52
0
Order By: Relevance
“…Furthermore, H3K27me3 was also modestly elevated (Fig. 5E), consistent with an essential role for H2AK119ub1 in shaping H3K27me3 at Polycomb target gene promoters (Blackledge et al 2014; Cooper et al 2014; Kalb et al 2014; Illingworth et al 2015; Blackledge et al 2020; Tamburri et al 2020). In contrast, at the subset of Polycomb target genes that become derepressed in the absence of BAP1, the levels of H2AK119ub1 and H3K27me3 at their promoters remained largely unchanged (Fig.…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, H3K27me3 was also modestly elevated (Fig. 5E), consistent with an essential role for H2AK119ub1 in shaping H3K27me3 at Polycomb target gene promoters (Blackledge et al 2014; Cooper et al 2014; Kalb et al 2014; Illingworth et al 2015; Blackledge et al 2020; Tamburri et al 2020). In contrast, at the subset of Polycomb target genes that become derepressed in the absence of BAP1, the levels of H2AK119ub1 and H3K27me3 at their promoters remained largely unchanged (Fig.…”
Section: Resultssupporting
confidence: 67%
“…Chromatin-modifying enzymes can function at defined gene regulatory elements to support cell type-specific gene expression patterns (Atlasi and Stunnenberg 2017; Yadav et al 2018). Their recruitment to these sites often relies on DNA- and chromatin-binding activities (Smith and Shilatifard 2010), and these mechanisms underpin how PRC1 creates high-level enrichment of H2AK119ub1 at Polycomb target gene promoters to enable repression (Endoh et al 2012; Blackledge et al 2015; Fursova et al 2019; Scelfo et al 2019; Blackledge et al 2020; Tamburri et al 2020; Cohen et al 2020). In addition to this punctate pool of H2AK119ub1, we and others have recently discovered that PRC1 also places low levels of H2AK119ub1 broadly throughout the genome (Lee et al 2015; Kahn et al 2016; Fursova et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ubiquitination of histone H2A is mediated by three E3 ligase complexes in a site- specific manner. While the ubiquitin conjugation on K119 is the most prevalent form catalyzed by the polycomb repressive complex 1 (PRC1) (Tamburri et al, 2020), H2A can also be mono- ubiquitinated on K13 and K15 by RNF168/RNF8 or on K125, K127, and K129 by BRCA1 in response to DNA damage (Horn et al, 2019; Kalb et al, 2014; Uckelmann and Sixma, 2017). As histone H2AubK119 IBs only revealed a moderate increase in Brap deficient cells or tissues relative to controls (Figure 5J, Figure 6A, and Figure S3A), H2A in Brap deficient cells and tissues must be additionally ubiquitinated on residues other than K119 by RNF168 and/or BRCA1.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting this model, ncPRC1-mediated H2AK119ub1 is central to the role of JARID2 in promoting H3K27me3 during X-chromosome inactivation (Almeida et al, 2017; da Rocha et al, 2014). Furthermore, the loss of H2AK119ub1 in mouse embryonic stem cells (ESCs) lacking ncPRC1 function leads to a partial reduction in the levels of core PRC2 members and H3K27me3 at Polycomb target genes (Blackledge et al, 2019 preprint; Tamburri et al, 2019 preprint; Fursova et al, 2019; Scelfo et al, 2019). Recent studies have identified that PRC2 recruitment predominantly occurs via its targeting to unmethylated CpG islands, both directly by Polycomb-like proteins and indirectly by JARID2 via its association with ncPRC1-mediated H2AK119ub (Healy et al, 2019; Højfeldt et al 2019).…”
Section: The Molecular Activities Of Prc2 In Mammalian Cellsmentioning
confidence: 99%